Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Mort ou fif: la face cachée du suicide chez les garçons - Dorais, Michel; Lajeunesse, Simon Louis (Des hommes et des femmes en changement, 2000)
A partir de témoignages et récits de vie, cet ouvrage met en lumière la relation entre le mépris et l'ostracisme dont sont victimes les adolescents homosexuels ou considérés comme tels et leur haut taux de suicide. Une version revue et corrigée d'un document publié par le Centre de recherche sur les services communautaires de l'Université Laval (octobre 2000).
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques